God's Work, Our Hands. Issue 2 (8th June 2016) - Deifelt, Wanda
Abstract: This essay offers a systematization of the various contributions to this issue, highlighting commonalities and creative tensions. Using Martin Luther's two‐kingdom theory as a framework, the leading question is the role of humanity in restoring creation and the deliberation that this ethical imperative—to carry out works of love on behalf of the neighbor (which includes creation itself)—might entail.